Geographic Variation in Diagnostic Ability and Quality of Care Metrics: A Case Study of Ankylosing Spondylitis and Low Back Pain - Jason Shafrin PhD; Jenny Griffith PharmD; Jin Joo Shim MS; Caroline Huber MPH; Arijit Ganguli PhD, MBA; Wade Aubry MD (SAGE Publishing, 2017)
Studies examining geographic variation in care for low back pain often focus on process and outcome measures conditional on patient diagnosis but generally do not take into account a physician's ability to diagnose the root cause of low back pain. In our case study, we used increased detection of ankylosing spondylitis-a relatively rare inflammatory back disease-as a proxy for diagnostic ability and measured the relationship between ankylosing spondylitis detection, potentially inappropriate low back pain care, and cost. Using 5 years of health insurance claims data, we found significant variation in ankylosing spondylitis detection across metropolitan statistical areas (MSAs), with 8.1% of the variation in detection explained by a region's racial composition. Furthermore, low back pain patients in MSAs with higher ankylosing spondylitis detection had 7.9% lower use of corticosteroids, 9.0% lower use of opioids, and 8.2% lower pharmacy cost, compared with patients living in low-detection MSAs.